2004
DOI: 10.1079/phn2004617
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and body mass index in HIV-positive and HIV-negative drug abusers of Hispanic ethnicity

Abstract: Objective: Malnutrition in drug abusers has been attributed to poor diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 29 publications
1
41
2
6
Order By: Relevance
“…Data describing this cohort, including details on dietary intake, weight and BMI, have been published elsewhere 1 . There were 286 participants enrolled in the study as of 31 December 2003.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data describing this cohort, including details on dietary intake, weight and BMI, have been published elsewhere 1 . There were 286 participants enrolled in the study as of 31 December 2003.…”
Section: Resultsmentioning
confidence: 99%
“…We recently published data from a study locally known as the BIENESTAR study, showing that Hispanic men infected with HIV who were drug abusers had a lower body mass index (BMI) than HIV-positive men who were not drug abusers. Reported energy intake could not explain the difference in BMI among the men 1 . These findings, consistent with previous studies conducted in other populations by our own group 2 and others 3,4 , support the notion that diet alone cannot entirely explain the lower weight of drug abusers.…”
mentioning
confidence: 79%
“…The multidimensional tools collect data on actual food consumed by individuals or households over a set period of time and provide detailed data about energy, macronutrient and micronutrient intake and/or food groupings. Food consumption measures are often used in combination with each other [92,93]. The major advantage of using these tools is that they can provide a much more complete picture of dietary intake, both in terms of what is eaten and how much of it.…”
Section: Multidimensional Measuresmentioning
confidence: 99%
“…Onyango et al [70] used a combination of 24-h recall and FFQ with HIV affected and non-affected households in Kenya and showed that the percentage of RDA consumed for almost all nutrients were higher for the non-HIV-affected households than for those with HIV. 24-h dietary recalls have also been used in the context of HIV-positive and negative drug using cohorts in the US, in combination with other food consumption measures, to ascertain possible association between BMI and dietary intake [93].…”
Section: -H Recallmentioning
confidence: 99%
See 1 more Smart Citation